Self-evaluation in perspective of Surah Al-Isrā verse 14th - Kasmah Usman; Achmad Abubakar; Muhsin Mahfudz (Jurnal Penelitian dan Evaluasi Pendidikan, 2021)
This paper describes, knows, understands, and analyzes self-evaluation from the perspective of surah Al-Isrā verse 14. Self-evaluation in psychology is called self-introspection, which means self-correction, while in Islam, it is called muḥāsabah or muḥāsabah al-nafṣ. Muḥāsabah, in the person of a Muslim in particular, is an attempt to count and evaluate himself, how many sins he has committed and what good he has not done. This study is qualitative research under the literature study method, which focuses on the question of self-evolution from the perspective of surah Al-Isra verse 14. The data source comes from the ministry of religious affairs' translation of the Qur'an, and books related to self-evaluation contain self-evaluation from surah Al-Isra' verse 14. Data were analyzed using the qualitative data analysis method. Self-evaluation in QS Al-Isra': 14 refers to the word al-ḥisāb, if an evaluation may be done by oneself on all the deeds that have been done. Explaining this, in surah Al-Isrā' verse 14, Allah evaluates His creatures on the day of reckoning (the trial of the Here-after). Therefore, it is a man who is commanded to judge his own deeds. If it is associated with the point of evaluation of education, the meaning of al-ḥisāb indicates that the assessment results depend on the intensity of the subject in completing the exam question. Therefore, the task of educators is to motivate the subject of the learner to learn and maximum when completing the exam question seriously.